Single board re-spin for testing bridge transducer products - Frances D. de la Rama; Marwin L. Tocama; Glenn N. Ortiz; Mark Joseph B. Enojas (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Integrated circuit (IC) testing involves equipment and product interface board setup. Complex interfaces and obsolete components are some of the factors affecting the board functionality which results in manufacturing downtime. The legacy boards must be simplified so that it needs advanced tools for the lay-out and designing of test boards. This study proposes a solution for board functionality issues by re-spinning the legacy two-board interface into a single board interface. It converts the standard use of boards and standard contacting to single board interface (SBI) and plunge-to-board (PTB) contacting. As a result, the setup time is improved, minimizing board and system repair due to mismatch and contact issues. The board endorsement for contact issues were trimmed from 82 to 46 counts. Other board related issues are decreased by 60% based on the analysis of the correlation in the processes. Additionally, mismatches, which are system issues, are lessened which promotes fixtures maintainability.